3D printing of a tough double-network hydrogel and its use as a scaffold to construct a tissue-like hydrogel composite. Issue 3 (4th January 2022) - Du, Cong; Hu, Jian; Wu, Xinyu; Shi, Huimin; Yu, Hai Chao; Qian, Jin; Yin, Jun; Gao, Changyou; Wu, Zi Liang; Zheng, Qiang
Abstract : 3D printed tough hydrogel constructs with high fidelity and stability are prepared by extrusion-based printing and further used as scaffolds filled with a cell-laden soft gel to develop a tissue-like hydrogel composite. Abstract : To mimic biological tissues with high toughness such as cartilage, it is highly desired to fabricate stable and tough hydrogels with intricate shapes to act as a structural support. Extrusion-based 3D printing is a promising method to fabricate 3D scaffolds with various architectures; however, printing tough hydrogel structures with high fidelity and resolution is still a challenge. In this work, we adopt the fast sol-to-gel transition of κ-carrageenan in the solution of acrylamide upon cooling to fix the printed scaffolds and polymerize the precursor solution to form the second network. The printed constructs of κ-carrageenan/polyacrylamide double-network gels are toughened by soaking in an aqueous solution of zirconyl chloride to form coordination complexes between the Zr 4+ ions and sulfate groups of κ-carrageenan. The obtained hydrogels are stable in water and possess good mechanical properties, with a tensile breaking stress of 1–2 MPa, breaking strain of 100–150%, and Young's modulus of 4–10 MPa. The printed grid can hold 150 times its own weight. 3D printed constructs with a high aspect ratio and shape fidelity are obtained by optimizing the printing parameters. Furthermore, a biomimetic strategy is applied to construct a hydrogel composite by filling the printed tough hydrogel scaffold with a cell-laden fibrin hydrogel as the soft substance. Chondrocytes in the hydrogel composite maintain high viability after cyclic compression, demonstrating the load-bearing capacity of the tough scaffold and favorable microenvironment for cells provided by the embedded soft fibrin gel. We envision that this printing strategy for hydrogel constructs with high toughness and good stability, as well as the method to form tough–soft hydrogel composites, can be extended to other systems to develop structural elements and scaffolds towards applications in biomedical devices and tissue engineering.